Accuracy of the Velotron Ergometer and SRM Power Meter - Abbiss, C. R.; Quod, M. J.; Levin, G.; Martin, D. T.; Laursen, P. B. (International Journal of Sports Medicine, 2009)
The purpose of this study was to determine the accuracy of the Velotron cycle ergometer and the SRM power meter using a dynamic calibration rig over a range of exercise protocols commonly applied in laboratory settings. These trials included two sustained constant power trials (250 W and 414 W), two incremental power trials and three high-intensity interval power trials. To further compare the two systems, 15 subjects performed three dynamic 30 km performance time trials. The Velotron and SRM displayed accurate measurements of power during both constant power trials (<1% error). However, during high-intensity interval trials the Velotron and SRM were found to be less accurate (3.0%, CI=1.6-4.5% and -2.6%, CI=-3.2--2.0% error, respectively). During the dynamic 30 km time trials, power measured by the Velotron was 3.7±1.9% (CI=2.9-4.8%) greater than that measured by the SRM. In conclusion, the accuracy of the Velotron cycle ergometer and the SRM power meter appears to be dependent on the type of test being performed. Furthermore, as each power monitoring system measures power at various positions (i.e. bottom bracket vs. rear wheel), caution should be taken when comparing power across the two systems, particularly when power is variable.